Pengaruh Dividend Payout Ratio Dan Earning Per Share Terhadap Harga Saham PT Indo Tambangraya Megah Tbk Periode 2014-2024 - Nabill Muranda; Koes Indrakoesoema (Jurnal Intelek Insan Cendikia, 2026)
The purpose of this study is to determine the effect of Dividend Payout Ratio and Earning Per Share on stock prices at PT Indo Tambangraya Megah Tbk during the period 2014–2024. The research method used is associative quantitative research. The population of this study consists of the financial statements of PT Indo Tambangraya Megah Tbk. The sample includes income statements, stock prices, and the number of outstanding shares for the period 2014–2024.Data analysis techniques employed in this study include classical assumption tests, multiple linear regression analysis, coefficient of determination analysis, and hypothesis testing. The results show that partially, Dividend Payout Ratio does not have a significant effect on stock prices, as indicated by a t-value of −1.542 < t-table of 2.262 and a significance value of 0.162 > 0.05. Partially, Earning Per Share has a significant effect on stock prices, with a t-value of 6.463 > t-table of 2.262 and a significance value of 0.000 < 0.05. Simultaneously, Dividend Payout Ratio and Earning Per Share have a significant effect on stock prices, as evidenced by an F-value of 26.480 > F-table of 4.46 and a significance value of 0.000 < 0.05.Based on the R-square value of 0.836 or 83.6%, it indicates that Dividend Payout Ratio and Earning Per Share contribute 83.6% to stock price variations, while the remaining 16.4% is influenced by other variables not examined in this study